2020
DOI: 10.1093/ehjci/jeaa065
|View full text |Cite
|
Sign up to set email alerts
|

Association of aortic valve calcification and vitamin K antagonist treatment

Abstract: Aims  Vitamin K antagonists (VKAs) are suspected of causing aortic valve calcification (AVC). The objective of this study was to clarify whether patients undergoing VKA treatment have increased AVC scores compared to patients treated with new oral anticoagulants (NOACs) and patients who never have been treated with VKA/NOAC. Methods and results  We included participants from the population-based DANCAVAS trial (n = 15 048). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…104 105 Sønderskov et al recently demonstrated that among 14 604 participants within the Danish Cardiovascular Screening (DANCAVAS) trial, VKA use was associated with progression of aortic valve calcification, evidenced by a 6% increase in calcification with each year of treatment. 106 These results remained consistent after a sensitivity analysis excluding patients with cardiac risk factors on statins showed no progression of calcification in those taking direct oral anticoagulants.…”
Section: Metabolic Syndromementioning
confidence: 53%
“…104 105 Sønderskov et al recently demonstrated that among 14 604 participants within the Danish Cardiovascular Screening (DANCAVAS) trial, VKA use was associated with progression of aortic valve calcification, evidenced by a 6% increase in calcification with each year of treatment. 106 These results remained consistent after a sensitivity analysis excluding patients with cardiac risk factors on statins showed no progression of calcification in those taking direct oral anticoagulants.…”
Section: Metabolic Syndromementioning
confidence: 53%
“…6 There is some concern that chronic use of VKAs can result in native valvular calcification. 7 If a similar phenomenon is seen in the prosthetic valves, it can be detrimental for their durability. Further investigations and more data are warranted in these areas.…”
Section: Mechanisms Of Action For Coumadin and Direct Anticoagulantsmentioning
confidence: 99%
“…Valve tissues were obtained within 1 h after being removed from patients during surgical procedures. Clinical information was gathered and the aortic valve calcification (AVC) score of calcific patients was measured as reported (Sonderskov et al 2020). Briefly, calcification was defined as occurring in the leaflet of the valve, the sinus of Valsalva (beginning 6 mm below the coronaries ostium).…”
Section: Human Aortic Valve Tissue Resourcementioning
confidence: 99%